Hubungan Paparan Asap Rokok dengan Kejadian Asma Bronkial di Poli Paru RSUD dr. H. Moch. Ansari Saleh Banjarmasin - Annisa, Nurul; Olviani, Yurida; Sary, Era Widia; Mulyani, Sri (Jurnal Siti Rufaidah, 2025)
Bronchial asthma is a chronic inflammatory disease of the airways that is often triggered by exposure to cigarette smoke, both active and passive. This exposure contains harmful substances such as nicotine, tar, and carbon monoxide that can irritate the airways, increase inflammation, and worsen asthma symptoms. This study aims to determine the relationship between cigarette smoke exposure and the incidence of bronchial asthma in patients at the Pulmonary Polyclinic of Dr. H. Moch. Ansari Saleh Regional General Hospital, Banjarmasin. The research method used a quantitative approach with a cross-sectional design. A sample of 47 patients was selected through purposive sampling according to the inclusion criteria. Data were collected through questionnaires and medical records, then analyzed using the Chi-Square test (α = 0.05). The results showed that the majority of respondents were passive smokers (61.70%), had family members who smoked (57.45%), and were exposed to cigarette smoke daily (55.32%). All respondents had been diagnosed with asthma by medical personnel, and 91.49% reported worsening symptoms after exposure to cigarette smoke. The chi-square test results showed a significant association between cigarette smoke exposure and the incidence of bronchial asthma (p = 0.026). This finding confirms that cigarette smoke exposure is an important risk factor that must be avoided to prevent relapse and worsening of asthma. Therefore, patient and family education regarding the dangers of cigarette smoke, the implementation of smoke-free areas, environmental support, and smoking cessation programs need to be continuously improved as strategies for controlling bronchial asthma.